The Geometrical Relationship Between Ancient Hindu Technical Treatises and the Planning and Organization of Angkor Wat - Vacharee Svamivastu; Komsan Maleesee (My University, 2025)
Angkor Wat is the supreme masterpiece of Khmer architecture, built by King Sūryavarman II during the 12th century A.D. Jane Przyluski hypothesized that Angkor Wat was the tomb of King Sūryavarman II. On the other hand, George Cœdès thought that Angkor Wat complex was habitation in the form of a celestial palace. According to Henri Parmentier, though the buildings and constructions in Angkor Wat temple complex are majestic, they are geometrically out of place. The temple complex is non-symmetrical, as the complex’s center is left-aligned. The above controversial opinions inspire a deep examination of the geometric system of the architectural and structural design of Angkor Wat. This research investigates the architectural planning and frame structures of Angkor Wat stone temple complex using a Hindu grid system. The study was based on field survey data of the temple complex and Hindu ancient texts, specifically the Vāstu Śāstra. PhotoModeler Pro5 and Polycam for iOS-4.0.5 were utilized to render three-dimensional (3D) images of the entire temple complex. The analysis finds the geometric code (suitable module) used in the planning of 2.75 m × 2.75 m in the metric system (1 Phyeam 1 Hat 1 Thnob in) the local Cambodian measuring system). The geometric code (2.75 m × 2.75 m) highlights the design diagram and construction of the temple complex. The research also unveiled the use of a center-shifting technique where the vertical axis running through the center is deliberately left-aligned, to avoid numerical fractions occurring in the grid modules. The technique gives rise to the asymmetry of the temple complex. The findings led to understanding the symbolic meaning of spatial organization of the layout and plan of Angkor Wat design, which was meant to be a suitable residence for the god on earth, the king, and his citizens. Moreover, it also means the final abode of King Sūryavarman II after his death, represented by the image of Lord Viṣṇu.
Keywords: Eurasian Exchange Networks